Aerospace series. Screw, 100° countersunk normal head, Spiral Drive Recess, short thread, in heat resisting steel FE-PA2601 (A286), passivated. Classification: 900 MPa (at ambient temperature)/650 °C. (8th April 2022) - British Standards Institution,
No abstract available